Correction: Intersecting paths: Corporate and green innovation in Chinese firms-A penal cointegration analysis. - ZhongJi Liu; Dan Hou; R M Ammar Zahid (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0295633.].